Electrodiagnostic evidence of suprascapular nerve recovery after decompression. Issue 2 (4th December 2018) - Feinberg, Joseph H.; Mehta, Priyesh; Gulotta, Lawrence V.; Allen, Answorth A.; Altchek, David W.; Cordasco, Frank A.; Potter, Hollis G.; Warren, Russell F.; Wickiewicz, Thomas L.; Wolfe, Scott W.
ABSTRACT: Introduction : The purpose of this study was to determine whether surgical arthroscopic decompression or ultrasound‐guided aspiration of a paralabral cyst would result in suprascapular nerve recovery from axonal regeneration based on electrodiagnostic testing. Methods : Nine patients with preoperative electromyography (EMG) evidence of suprascapular neuropathy due to paralabral cysts at the suprascapular or spinoglenoid notch were prospectively studied. Eight patients underwent arthroscopic surgical decompression, and 1 patient underwent ultrasound‐guided aspiration. Postoperative EMG was performed in all patients to evaluate nerve regeneration. Results : Three (33%) patients had cysts at the suprascapular notch, whereas 6 (67%) patients had cysts at the spinoglenoid notch. All patients showed complete electrophysiological recovery after decompression. Discussion : Decompression of paralabral cysts at the suprascapular or spinoglenoid notch resulted in postoperative EMG evidence of nerve recovery. Long‐term studies with a greater number of patients are required to elucidate time to recovery. Muscle Nerve 59 :247–249, 2019